Corrosion inhibition and adsorption properties of N-Phenylhydrazine-1,2-Dicarbothioamide on mild steel in hydrochloric acid - Shukla S.K.; Singh A.K.; Quraishi M.A. (My University, 2025)
Corrosion Inhibition of the mild steel in 1M HCl N-phenylhydrazine-12-dithiocarboamide (PDA) has been investigated using weight-loss, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. Inhibition efficiency increases with increase in inhibitor concentration, and solution temperature. Inhibition efficiency decreases with very slow rate with the increase of the immersion time and the acid concentration. The adsorption of PDA on mild steel in hydrochloric acid solution obeys Langmuir's adsorption isotherm model. Potentiodynamic polarization suggests that PDA acts as mixed type inhibitor. Thermodynamic parameters suggest the adsorption is spontaneous and exothermic process. The results obtained from the three methods used are in good agreement. © 2011 by ESG.